2006
DOI: 10.1007/s11095-006-0206-9
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Immunization with Anthrax Protective Antigen Protein Adjuvanted with Polyriboinosinic–Polyribocytidylic Acid Induced Strong Mucosal and Systemic Immunities

Abstract: This pI:C-adjuvanted rPA vaccine has the potential to be developed into an efficacious nasal anthrax vaccine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
45
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 43 publications
1
45
0
Order By: Relevance
“…These receptors not only recognize a number of specific components conserved among microorganisms, but are also capable of recognizing specific defensins as well as fragments of extracellular matrix proteins [1][2][3][4][5][6][7]. Since, the activation of macrophages or dendritic cells (DCs) through one or more of their TLRs enhances innate immunity and can modulate the subsequent development of antigen-specific adaptive immunity, some TLR ligands have been used as adjuvants in vaccine formulations administered parenterally to augment systemic immune responses [8][9][10][11]. Specific TLR ligands have been reported to promote the induction of both systemic and mucosal immune responses when co-administered with antigen intranasally [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These receptors not only recognize a number of specific components conserved among microorganisms, but are also capable of recognizing specific defensins as well as fragments of extracellular matrix proteins [1][2][3][4][5][6][7]. Since, the activation of macrophages or dendritic cells (DCs) through one or more of their TLRs enhances innate immunity and can modulate the subsequent development of antigen-specific adaptive immunity, some TLR ligands have been used as adjuvants in vaccine formulations administered parenterally to augment systemic immune responses [8][9][10][11]. Specific TLR ligands have been reported to promote the induction of both systemic and mucosal immune responses when co-administered with antigen intranasally [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Since, the activation of macrophages or dendritic cells (DCs) through one or more of their TLRs enhances innate immunity and can modulate the subsequent development of antigen-specific adaptive immunity, some TLR ligands have been used as adjuvants in vaccine formulations administered parenterally to augment systemic immune responses [8][9][10][11]. Specific TLR ligands have been reported to promote the induction of both systemic and mucosal immune responses when co-administered with antigen intranasally [9][10][11][12].*Corresponding author. Address: Department of Pathology, University of Utah Medical School, 30 North 1900 East, Salt Lake City, UT 84132, USA; Phone: 1-801-585-1522; Fax: 1-801-581-8946; e-mail: elena.enioutina@path.utah.edu.…”
mentioning
confidence: 99%
“…Although, to date, human trials of PA vaccines have used alum adjuvant (23,24), other adjuvants, including Ribi adjuvant formulation for parenteral formulations (25) and cholera toxin and poly(I·C) for intranasal formulations (26,27), have been shown to be effective in animal studies. Hence, use of alternative adjuvant technologies (28) may allow the development of moreeffective and better-tolerated PA vaccines.…”
mentioning
confidence: 99%
“…Treatment with ODN or PIC results in strong cytokine/chemokine induction, establishing an antiviral state within the host. Accordingly, ODN and PIC have been used as components of vaccine formulations to enhance the host's immune response (15)(16)(17)(18)(19)(20), and further studies have shown that adjuvants containing both ODN and PIC can enhance the immunogenicity of vaccines (21,22). Although ODN and PIC can each induce an antiviral immune response within the host, the responses differ in expression profile, cellular localization, and signaling pathways (23).…”
mentioning
confidence: 99%